2007
DOI: 10.1016/j.jcrs.2006.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the keratometric index: Large population-based study

Abstract: Modifying the keratometric index increased the accuracy of predicting the posterior corneal power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
60
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 20 publications
6
60
1
3
Order By: Relevance
“…1 Corneal power overestimation was always found in both eye models when an n k value of 1.3375 was used. These findings 1 and those in previous studies [2][3][4] show there is a need for a precise model to determine the most appropriate n k value for calculating P c with the keratometric approach. We developed and reported a fast, easy, and clinically applicable method for determining the most appropriate n k for the keratometric estimation in each specific case.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…1 Corneal power overestimation was always found in both eye models when an n k value of 1.3375 was used. These findings 1 and those in previous studies [2][3][4] show there is a need for a precise model to determine the most appropriate n k value for calculating P c with the keratometric approach. We developed and reported a fast, easy, and clinically applicable method for determining the most appropriate n k for the keratometric estimation in each specific case.…”
Section: Discussionsupporting
confidence: 62%
“…[2][3][4]9,11 The classic n k value of 1.3375 was proposed for convenience rather than for optical significance because it provided an agreement between a specific value of the anterior radius of curvature and the total P c (7.5 mm and 45.0 D). 10 Other n k values have been derived from schematic eye models, such as the value of 1.3315, which was derived from the Gullstrand schematic eye and recommended by Olsen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the TCP in this study gave higher astigmatism measurements than automated K or simulated K, which did not measure the posterior cornea. The use of a single keratometric index to compensate for posterior cornea might not reflect the true corneal astigmatism in all age groups 26,27 because the result might be different between ages. Furthermore, an earlier study 28 found a statistically significant difference in the amount of astigmatism between men (1.01 D) and women (1.06 D).…”
Section: Discussionmentioning
confidence: 99%
“…One is the approximation related to the equivalent refractive index. 35 Although the value chosen for the model was equivalent to that predicted by physiological measurements, 31 a fully customized model could be used that considers the posterior corneal surface, although the impact of introducing further experimental measurement errors should be evaluated. In addition, IOL placement prediction remains a challenge.…”
Section: Discussionmentioning
confidence: 99%